Analysis of Classical Poets’ Viewpoints about Editing Poetry and manipulating Stories with an Emphasis on Nezami Ganjavi's Works - Yasin Esmaeely (مطالعات زبانی و بلاغی)
Today, editing is a type of knowledge with a defined framework. In the process of editing, someone other than the author or the poet edits the created text from the linguistic and technical aspects and makes changes to it. The type of editing this research is concerned with is different from editing in the contemporary era. In this kind of editing, the poet manipulates and modifies his work and, according to his style and attitude, he makes changes during and after composition. In fact, the poem which is the result of inspiration and intuition, is manipulated. In Persian poetry, there have been poets such as Sanā’ī and Attār or Hafez, par excellence, who were not satisfied with their poetry in its original form and worked for its perfection. Nezāmi Ganjavi is one of the other poets who believed in the literary editing of the text, and himself applied edits to his poetry and coined the term Ghalat Kāri (working on the falsity) for it. This type of editing also includes alteration of stories for reasons such as aesthetic preferences, moral considerations and avoiding repetition in the form of expression. There is another reason behind avoiding repetition, which relates to commonalities between a number of Nezāmi Ganjavi's stories and other poets and writers such as Ferdowsi. In addition to the poets, whose views are very important about this, writers have also expressed their views in this regard. Some writers have agreed with manipulation in poetry and some are against any kind of manipulation. These theories are sometimes expressed directly and sometimes are indirectly implied and should be understood through the principles and rules expressed for poetry. In this research, the editing in poetry has been investigated by emphasizing Nezāmi Ganjavi's works and his views.